2019
DOI: 10.26656/fr.2017.4(2).293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gum arabic (Acacia senegal) addition on physicochemical properties and sensory acceptability of roselle juice

Abstract: Roselle has a brilliant red colour, high in vitamins and has a unique flavour that makes it suitable for juice production. Meanwhile, Gum Arabic (GA) is the edible dried exudate attained from stem and branch of Acacia senegal that contains high dietary fibre which can serve as prebiotic. Therefore, the application of GA into roselle juice might promote health benefits to consumers. GA is categorised as hydrocolloid and its application might affect important properties and acceptability towards the product. Hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The moisture content of spray-dried cantaloupe powder significantly decreased with the addition of AG. This might be due to the increase in the concentration of AG which increased the total feed solids, thus reducing the total moisture (Tuan Azlan et al, 2020). A similar finding was reported by Bhusari et al (2014) and Caliskan and Dirim (2016) who worked with tamarind pulp powder and spray-dried sumac extract powder, respectively.…”
Section: Moisture Content and Water Activitysupporting
confidence: 76%
“…The moisture content of spray-dried cantaloupe powder significantly decreased with the addition of AG. This might be due to the increase in the concentration of AG which increased the total feed solids, thus reducing the total moisture (Tuan Azlan et al, 2020). A similar finding was reported by Bhusari et al (2014) and Caliskan and Dirim (2016) who worked with tamarind pulp powder and spray-dried sumac extract powder, respectively.…”
Section: Moisture Content and Water Activitysupporting
confidence: 76%
“…The effect of gum Arabic concentration provides excellent protection on the antioxidant content of the sea grapes powder drink. It was also reported that research on rosella juice showed that increasing concentrations of gum Arabic could maintain antioxidant properties 34 . This finding aligns with Agatha et al ( 2021), who stated an increase in DPPH antioxidant activity and phenolic content by using a 10% Arabic gum concentration in a red dragon fruit kombucha powder drink product.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fermentation of GA by the intestinal bacteria reflects its prebiotic characteristic of GA and its capability of increasing the Bifido bacteria. Supplementation of the consumer with 10 gm of GA on daily basis can have prebiotic potential as reported by [4].…”
Section: Introductionmentioning
confidence: 96%